2020
DOI: 10.1097/cmr.0000000000000688
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and molecular features of subungual melanomas are site-specific and distinct from acral melanomas

Abstract: Subungual melanomas (SUM) arise beneath the nails of the hands and feet, and account for 0.7–3.5% of all malignant melanomas. Most studies include SUM in the category of acral melanoma, but understanding the specific features of SUM is critical for improving patient care. In this study, we performed a site-specific comparison of the clinical and molecular features between 54 cases of SUM and 78 cases of nonsubungual acral melanoma. Compared to patients with acral melanoma, patients with SUM were younger at dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
30
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(54 citation statements)
references
References 45 publications
6
30
2
Order By: Relevance
“…In particular, BRAF-mutated cases were correlated with a lower frequency of gains in the CCND1 locus compared to TWT AMs (29% and 61%, respectively), as reported by Curtin and colleagues [18]. No BRAF mutations were detected in subungual melanomas, confirming its rarity in this site [26,27]. The importance of this pathway in AM was also highlighted by the high percentage of cases with gains in the BRAF locus (47%).…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations
“…In particular, BRAF-mutated cases were correlated with a lower frequency of gains in the CCND1 locus compared to TWT AMs (29% and 61%, respectively), as reported by Curtin and colleagues [18]. No BRAF mutations were detected in subungual melanomas, confirming its rarity in this site [26,27]. The importance of this pathway in AM was also highlighted by the high percentage of cases with gains in the BRAF locus (47%).…”
Section: Discussionsupporting
confidence: 66%
“…According to the literature, the rate of BRAF-mutated AMs (35%) was lower than those reported for the other non-acral cutaneous melanomas [1,15,17,18]. However, it was higher than those usually found in this melanoma subtype, which rarely exceeds 20% of cases [15,16,24,25,27]. An explanation could be the fact that the present series only included Italian patients.…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…Several recent studies suggest that nail apparatus melanoma (NAM) differs from non‐nail apparatus acral melanoma (NNAM) 23–25 . Holman et al 23 . reported that NAM and NNAM show clinical and molecular differences.…”
Section: Discussionmentioning
confidence: 99%